1989
DOI: 10.1159/000293556
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Vaginosis Is Not a Simple Ecological Disorder

Abstract: Eighty-four patients with bacterial vaginosis were examined in an open randomized trial, the aim of which was to define clinical results and the microbiological panorama after topical treatment for 1 week with either an acetic acid jelly (A), an estrogen cream (B), a fermented milk product (C) or metronidazole (D). After exclusion because of chlamydia infection (15 cases) or for other reasons, 61 cases remained for complete evaluation 4 weeks after the start of treatment. Clinical cure was obtained in 3 cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 11 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…Two possible hypotheses arise concerning the lack of permanence of acetic acid: quick absorption and metabolism by the vaginal mucosa; and poor adhesiveness of the gel to the vaginal mucosa and clearance of the product by vaginal discharge. In a randomized clinical trial using an acetic acid gel compared with metronidazole, Fredricsson and co-workers [11] obtained cure in only three of 17 cases treated with acetic acid gel, whereas 13 of 14 were cured with oral metronidazole. It appears to us not very appropriate to compare the efficacy of an antibiotic versus an acidifying agent, especially without selecting an appropriate patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Two possible hypotheses arise concerning the lack of permanence of acetic acid: quick absorption and metabolism by the vaginal mucosa; and poor adhesiveness of the gel to the vaginal mucosa and clearance of the product by vaginal discharge. In a randomized clinical trial using an acetic acid gel compared with metronidazole, Fredricsson and co-workers [11] obtained cure in only three of 17 cases treated with acetic acid gel, whereas 13 of 14 were cured with oral metronidazole. It appears to us not very appropriate to compare the efficacy of an antibiotic versus an acidifying agent, especially without selecting an appropriate patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Fredricsson et al [90] conducted an open-label trial to compare the cure rates of 61 women with BV given one of four intravaginal products. Patients were diagnosed with BV if ≥3 Amsel criteria were present.…”
Section: Probiotics To Prevent and Treat Urogenital Infectionsmentioning
confidence: 99%
“…Some clinical and demographic variables have been reported to correlate with post-treatment recurrence of BV, including a past history of BV and a regular sex partner (Bradshaw et al, 2006). In addition, it was reported that several Lactobacillus species, including L. gasseri, L. brevis , and L. acidophilus , could reduce BV recurrence (Neri et al, 1993; Shalev et al, 1996; Anukam et al, 2006), although such findings were controversial (Fredricsson et al, 1989; Hallen et al, 1992; Eriksson et al, 2005). Of note, these studies all used simple, traditional methods of clinical microbiology, which are inadequate to characterize the complex and dynamic composition of vaginal microbiota (Ravel et al, 2011).…”
Section: Introductionmentioning
confidence: 99%